Career self-management : evaluation of an intervention with culturally diverse samples - Silva, Ana Daniela (2011)
“Career Self-Management Seminar”, in its version B, (CSMS-B, [1]), is a specialized psychological intervention model designed to support academics in career exploration, goal setting, design and implementation of action plans, and monitoring and feedback obtaining, in order to facilitate career problem solving and decision making ([2]; [3]; [4]). This study aims to present and discuss the evaluation of the intervention outcomes, in a group of Portuguese young adults (EG1=16), and in a group of Mozambican young adults (EG2=16), in comparison with a control group (CG=16). Its effects on cognitive, behavioral, and emotional dimensions of the career exploration process, and on the type of participants’ career concerns were evaluated through the completion of the self-report measures Career Exploration Survey (CES, [5]; EEV, adapt. by [6]) and Adult Career Concerns Inventory (ACCI, [7]; IPC, adapt. by [8]), respectively, in two different moments in time. Implications are drawn for the design of specialized career intervention models adjusted to clients’ multicultural characteristics.